FiTRO Dyne Basic - a simple system for the assessment of strength capabilities and feed back monitoring of weight training. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2008)
Two functionally identical versions of FiTROdyne Basic are available. One features microcomputer unit with smaller LED display (FiTROdyne Basic LCD) and another one microcomputer unit with larger LED display (FiTROdyne Basic LED). Better visibility of LED unit is of advantage if the system is intended to use for a feedback monitoring of resistance training. In weight exercise, the muscles lift a mass m by applying a force F (equal to m.g) at velocity v producing power P (equal to F.v). In current practice in strength training, attention is largely directed to the weight itself, whereas velocity and power are usually neglected. However, these parameters may be of great importance, not only for weight training, but for the assessment of strength capabilities. FiTRODYNE represents simple easy to use system to be used for the registration of velocity and power in concentric phase of weight exercise. The FiTROdyne system measures upward vertical velocity of the exercise weight by means of mechanically coupled sensor. Using known mass (input prior to the exercise), the system determines the power in the concentric phase of the weight exercise (equal to m x g x v). In this way, the system provides all the basic parameters of a weight exercise, i.e. force, velocity and power. A barbell or weight exercise machine equipped with such a system is effectively a simple dynamometer. The parameters obtained allow not only monitoring of fatigue during exercise set, but also sophisticated assessment of strength capabilities.